Abundance, distribution and habitat preference of Hippocampus guttulatus and Hippocampus hippocampus in a semi‐enclosed central Mediterranean marine area. (20th January 2014) - Gristina, Michele; Cardone, Frine; Carlucci, Roberto; Castellano, Laura; Passarelli, Sergio; Corriero, Giuseppe
Abstract Population abundance, distribution and habitat preference of the Mediterranean sympatric seahorses Hippocampus guttulatus and Hippocampus hippocampus were investigated in a semi‐enclosed sea system (Apulian coast, Ionian Sea). A total of 242 individuals of seahorses were sighted in the 11 transects surveyed in summer 2011. Hippocampus guttulatus (n = 225) were 14 times more abundant than H. hippocampus (17). The mean abundance of H. guttulatus for all the pooled sites was 0.018 m−2 (SE ± 0.003) ranging from a maximum of 0.035 (SE ± 0.007) to a minimum of 0.008 (SE ± 0.002). The size structure of long‐snouted seahorse shows a population ranging from 7 to 14 cm (SL) with a peak at 10 cm (TL). Juveniles (96.0 ± 8.0 mm) represent a significant fraction of the population, accounting more than 21% of the sighted individuals. In Mar Piccolo, H. guttulatus is able to shelter both in monotonous habitats, including the algal beds, and diversified ones, such as the rich filter‐feeder communities that colonize hard substrates. By contrast, H. hippocampus is mainly associated with habitats of low complexity. Today, the Mar Piccolo di Taranto is among the most heavily polluted water bodies in South Italy, with trace metals, hydrocarbons, pesticides and organic wastes affecting both biotic and abiotic matrices. However, despite the high level of degradation, the presence of a large mussel farm has avoided the impact of towed fishing gears, and eutrophication of water bodies has ensured a high trophic level that supports large crustacean populations, potential prey for seahorses.